(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article focuses on media literacy as a crucial competency for the 21st century. It portrays media literacy as a pivotal stage in the progression from information literacy to media culture. The research outlines various domains of media education and provides examples of specific skills cultivated throughout the learning process. Additionally, the author highlights actionable strategies that can be implemented in university-level media literacy instruction.